In vitro testing of combined hydroxychloroquine and azithromycin on SARS-CoV-2 shows synergistic effect - Andreani, Julien; Le Bideau, Marion; Duflot, Isabelle; Jardot, Priscilla; Rolland, Clara; Boxberger, Manon; Wurtz, Nathalie; Rolain, Jean-Marc; Colson, Philippe; La Scola, Bernard; Raoult, Didier (Microbial pathogenesis, 2020)
Human coronaviruses SARS-CoV-2 appeared at the end of 2019 and led to a pandemic with high morbidity and mortality. As there are currently no effective drugs targeting this virus, drug repurposing represents a short-term strategy to treat millions of infected patients at low costs. Hydroxychloroquine showed an antiviral effect in vitro. In vivo it showed efficacy, especially when combined with azithromycin in a preliminary clinical trial. Here we demonstrate that the combination of hydroxychloroquine and azithromycin has a synergistic effect in vitro on SARS-CoV-2 at concentrations compatible with that obtained in human lung. •SARS-CoV 2 emergence and spreading need to found urgently therapeutics.•Drug repurposing is the best strategy for quick therapeutic response.•Azithromycin and hydroxychloroquine shows synergistic effect on replication.•Concentrations of drugs are more compatible with in vivo concentrations.